HYPERBARIC OXYGENATION AS THE PRETREATMENT AND THERAPY IN ISCHEMIA-REPERFUSION INJURY - Pejovic, Teodora; Kovacevic, Sanjin; Brkic, Predrag; Nesovic Ostojic, Jelena (HEALTH CARE, 2022)
Tissue ischemia means insufficient blood flow to a certain area of ​​the body. Interruption of the arterial blood supply leads to an imbalance between metabolic supply and demand and the development of tissue hypoxia. Tissue hypoxia induces metabolic changes that result in inflammation, increased production of reactive oxygen species, and cell death. If adequate blood flow is established in the ischemic tissue, there will be an increase in cellular damage, which is referred to as ischemic-reperfusion injury. Ischemia and ischemia-reperfusion injury are at the root of numerous diseases widely present in modern society, such as myocardial infarction, cerebral insult, acute kidney injury. For now, there is no way to directly affect cellular hypoxia, but the clinical treatment of hypoxic conditions is aimed at modulating global hypoxemia and increasing the amount of oxygen dissolved in the blood. Hyperbaric oxygenation (HBO) is a treatment during which the patient breathes 100% oxygen under a pressure of at least 1.4 atmospheres. Although the use of hyperbaric therapy was recorded as early as the 17th century, today this treatment is approved for a few indications.